Morpho-physiological and fiber quality evaluation of cotton genotypes under normal sowing condition (Zoo Botanica, 2025)
Cotton (Gossypium hirsutum L.) is a key fiber crop with significant economic importance, yet Pakistan has recently experienced declining production and yield. There is a need to evaluate cotton germplasm with enhanced yield and quality traits. For this purpose, 79 cotton genotypes were sown at the Cotton Research Station, Vehari under Randomized Complete Block Design (RCBD) to assess morphological, physiological, and fiber quality traits, including plant height, bolls per plant, sympodial branches, boll weight, ginning outturn, seed cotton yield, cell membrane thermostability, pollen viability, fiber length, fiber strength, and fineness. Significant phenotypic variation was observed among genotypes for most traits. Correlation and principal component analysis revealed strong positive associations among yield-related and physiological traits, while fiber quality traits clustered separately. Heat map and mean value analyses identified superior genotypes, with G5, G24, G32, G44, G46, G52, and G60 exhibiting the highest fiber strength and promising performance for seed cotton yield, pollen viability, and cell membrane thermostability. These genotypes constitute an important gene pool for breeding programs focused on improving yield, fiber quality, and heat stress tolerance in cotton. The study provides a foundation for selecting superior parents for future cotton improvement under normal and stress-prone environments.
Keywords: Biplot analysis; fiber quality; Gossypium hirsutum; heat map; physiological traits